ANALISIS ELEMEN GAME DALAM TAMAGOTCHI PIX SEBAGAI IMPLEMENTASI HEWAN PELIHARAAN VIRTUAL - Kessy Situmorang (JADECS (Journal of Art, Design, Art Education and Culture Studies))
Abstact: Virtual pets are characters that have animal-like characteristics that can create an emotional connection with the user. One toy that belongs to the virtual pet genre is the Tamagotchi. Tamagotchi is an educational-based toy that is similar to raising animals directly by raising one pet character from baby to adult and then returning it to its home planet in good condition. Users can carry out the tasks given to learn more about how to care for animals with care and learn to be more disciplined. The Tamagotchi Pix is one of the newest versions of the Tamagotchi which was released in mid-2021. This device provides a color screen, touchscreen buttons and a camera to create deeper interaction between the user and the Tamagotchi character. By conducting qualitative research methods, the features contained in Tamagotchi Pix can show how Tamagotchi Pix fulfills Teresa Dillon's eight game elements. Apart from fulfilling the game elements from Teresa Dillon, Tamagotchi Pix also provides users with something more than just a virtual pet using the device's sophistication with a camera.